PERBANDINGAN KEBAHAGIAAN PADA WANITA YANG MELAKUKAN PERAWATAN KECANTIKAN DAN YANG TIDAK MELAKUKAN PERAWATAN KECANTIKAN UNTUK MENGUBAH PENAMPILAN DIRI - Ardhi Mohamad; Anna Armeini Rangkuti (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
Abstract The aim of this study is to answer the difference of happiness between women that apply beauty treatments and women whom is not to alter the appearance of the self. This research conducted on October 2013-January 2014. This study used comparative quantitative study methods. Incidental sampling was used as the sampling techniques in this research. The subject of this study are a total of 140 respondents. The happiness variable was assesed using scale of happiness made by the researchers. Data analysis technique used to test the hypothesis is with measuring the t test using SPSS 17.00. The result of this study showed that there is a difference of happiness between women that apply beauty treatment and whom is not to alter the appearance of the self with a significance value of 0,025. This study also also showed that women whom is not apply beauty treatments are having higher mean value than the women that apply beauty treatments with the t value of -2,272. Keywords : happiness, women, beauty treatment